Drastic enhancement in the rate and cyclic behavior of LiMn2O4 electrodes at elevated temperatures by phosphorus doping. (1st October 2019) - Hou, Yaolin; Chang, Kun; Tang, Hongwei; Li, Bao; Hou, Yan; Chang, Zhaorong
Abstract: Herein we provide an effective strategy for drastically improving the cyclic behavior and rate capability of an LiMn2 O4 (LMO) electrode at elevated temperature through P element doping. The P-doped LiMn2 O4 materials are characterized by X-ray diffraction, scanning electron microscopy, and X-ray photoelectron spectrometry analysis. The results show that the P element is effectively and uniformly doped within the LiMn2 O4 crystal lattice and is beneficial for growth of the truncated octahedral crystal structure. The electrochemical results reveal that P doping can greatly improve the cycling performance of LiMn2 O4 electrodes, especially improving the rate capability at elevated temperatures. At a high 10C rate of current density and 55 °C, the optimized LMO (1.5 wt% P) electrode shows the highest initial specific capacity of 101.2 mAh g −1, which become 74.4 mAh g −1 after 500 cycles, corresponding to 73.5% capacity retention. Under similar conditions, the LMO (2.5 wt% P) electrode shows an initial discharge capacity of 78.5 mA g −1, which become 72.2 mAh g −1 after 500 cycles, corresponding to 92.3% capacity retention. Graphical abstract: Image 1 Highlights: P-doped LiMn2 O4 was first successfully synthesized and investigated. Phosphorus was effectively and uniformly doped within the LiMn2 O4 crystal lattice. The P fluxing effect enhanced the truncated octahedral crystal structure growth. P-doped LiMn2 O4 has improved electrochemical performance at elevated temperatures.